2011
DOI: 10.1007/s10812-011-9459-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of photosensitized singlet oxygen generation and photophysical characteristics of chlorin e 6 in photolon ointment

Abstract: We have used luminescence and absorption spectroscopy to study the dynamics of photosensitized singlet oxygen generation and the photophysical characteristics of chlorin e 6 in Photolon ointment. We have shown that dimethylsulfoxide and polyethylene glycol 400, in concentrations comparable with their content in the ointment form of the drug Photolon, do not lead to appreciable changes in the spectral characteristics of chlorin e 6 . Substantial changes in the photophysical characteristics of the photosensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This shift is commonly ascribed to the transfer of Ce6 ring from water to the less polar microenvironment ( e.g . for Ce6 complexes with serum proteins and PVP or its solutions in ethanol or DMSO ). It is known that Pluronic F127 forms small micelles ( R h ~11 nm ) in water solution.…”
Section: Resultsmentioning
confidence: 99%
“…This shift is commonly ascribed to the transfer of Ce6 ring from water to the less polar microenvironment ( e.g . for Ce6 complexes with serum proteins and PVP or its solutions in ethanol or DMSO ). It is known that Pluronic F127 forms small micelles ( R h ~11 nm ) in water solution.…”
Section: Resultsmentioning
confidence: 99%
“…The porphyrin-photosensitized oxygenation of biologically important compounds (photodynamic action) is widely used in medicine for treatment of cancer and infectious diseases (photodynamic therapy, PDT). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Usually, oxygenation is due to the reactivity of singlet oxygen, which is generated by triplet molecules of photosensitizers. In some cases, the triplet molecules can oxidize biosubstrates directly, but the efficiency of the porphyrin involvement in these reactions is usually very low.…”
Section: медные комплексы хлоринов производных хлорофилла а как потmentioning
confidence: 99%
“…[1,2] It has been shown that metal free chlorophyll derivatives: pheophytin and pheophorbide a, chlorin e 6 , chlorin p 6 and their complexes with some metals are effective photodynamic sensitizers. Certain compounds from this group are recommended for clinical use in PDT (Phoscan, Photoditazin, Photolon, Radachlorin) ( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and references cited therein). To our knowledge, the systematic studies of the photodynamic activity of copper chlorins have never been carried out, because the lifetime of the triplet state in copper complexes is known to be several orders shorter than that of the metal-free analogs, [17][18][19] that should cause the strong reduction in the efficiency of singlet oxygen generation.…”
Section: медные комплексы хлоринов производных хлорофилла а как потmentioning
confidence: 99%
“…The solution concentrations were 10 -5 M. Mass spectra were recorded in a Finnigan LCQ/Electrospray instrument (USA). Luminescence properties of singlet oxygen were determined using a high-sensitivity laser fluorometer for recording accumulation kinetics and luminescence quenching at 950-1400 nm with nanosecond time resolution [17]. The high-sensitivity fluorometer was constructed using a Hamamatsu photomultiplier photodetector with a semiconducting photocathode based on InP/InGaAsP.…”
Section: Experimental Synthesis Norborn-5′-eno[b]tetraazachlorin (Hmentioning
confidence: 99%
“…The excitation was carried out at 531 nm by 0.7-nsec laser pulses at repetition rate 1 kHz [17]. Quantum yields of photosensitized singlet oxygen formation were determined by a relative method.…”
Section: Experimental Synthesis Norborn-5′-eno[b]tetraazachlorin (Hmentioning
confidence: 99%